The Effect of Social Media Influencer and Brand Image On Online Purchase Intention During The Covid-19 Pandemic - Feby Eka Vivi Setio Putri; Monika Tiarawati (Ilomata International Journal of Management, 2021)
The Covid-19 pandemic that has hit the whole world has caused economic problems. Household consumption or the purchasing power of the Indonesian people fell very deeply. Whereas consumption or people's purchasing power supports 60% of the Indonesian economy. Therefore, the pattern of marketing is changed by doing marketing online. Companies use social media influencer to advertise their products. This study was conducted to analyze the impact of social media influencers and brand image on online consumer purchase intentions. The criteria for respondents in this study were women aged 18 years and over who followed Tasya Farasya's Instagram and knew about Maybelline products. Partial Least Square (PLS) is used to analyze the respondent's data that has been collected. The results of this study indicate that social media influencers have no positive and significant effect on online purchase intentions. Meanwhile, brand image has a positive and significant effect on online purchase intentions.